Achieving Ammonium Removal Through Anammox-Derived Feammox With Low Demand of Fe(III) - Hu, Lanlan; Cheng, Xiaohui; Qi, Guangxia; Zheng, Min; Dang, Yan; Li, Jiyun; Xu, Kangning (Frontiers in Microbiology, 2022)
Feammox-based nitrogen removal technology can reduce energy consumption by aeration and emission of carbon dioxide. However, the huge theoretical demand of Fe(III) becomes a challenge for the further development of Feammox. This study investigated an anammox-derived Feammox process with intermittent dosage of Fe2O3 and proposed a novel approach to reduce the Fe(III) consumption. Results showed that anammox genera Candidatus Brocadia and Candidatus Kuenenia in the seed anammox sludge significantly decreased after cultivation. Formation of N2 was the dominating pathway in Feammox while that of nitrite and nitrate could be neglected. Batch tests showed that specific Feammox activity of ammonium oxidation was 1.14‒9.98 mg N/(g VSS·d). The maximum removal efficiency of ammonium reached 52.3% in the bioreactor with low dosage of Fe(III) which was only 5.8% of the theoretical demand in Feammox. The removal of ammonium was mainly achieved through Feammox while partial nitrification/anammox also played a role due to the non-power and unintentional oxygen leakage. The super low oxygen also responded for the low demand of Fe(III) in the bioreactor because it could trigger the cycle of Fe(III)/Fe(II) by coupling Feammox and chemical oxidation of Fe(II) to Fe(III). Therefore, anammox-derived Feammox can achieve the removal of ammonium with low Fe(III) demand at super low oxygen.